Strategy Formulation For PT Sido Muncul Tbk in Market Competition - Sugiarto, Shiefanny Delicia; Murhadi, Werner R. (SEAN Institute, 2024)
This research aims to analyze various strategic options that can be implemented by PT Sido Muncul. PT Sido Muncul is a company that operates in the field of natural health products such as herbal medicine and other herbal supplements. Up till now, various products from the company have spread widely throughout Indonesia constantly and have even entered the global market. The key concept of this research includes strategy formulation for the company and the results will show how the company's internal and external analysis produces strengths, weaknesses, opportunities and challenges (SWOT). This research will also present measurements through various other matrices such as EFE (External Factor Evaluation) and IFE (Internal Factor Evaluation), CPM (Competitive Profile Matrix), TOWS (Threats, Opportunities, Weaknesses, Strengths), SPACE (Strategic Position and Action Evaluation ), BCG (Boston Consulting Group), IE (Internal-External), GSM (General Strategic Matrix) and QSPM (Quantitative Strategic Planning Matrix). Based on the research results using the matrix measurements above, the strategy recommendation obtained for PT Sido Muncul is to carry out a market penetration strategy to reach an even larger market share. Through a market penetration strategy, apart from being able to increase competitiveness in a wider market, the company can also experience significant growth in the future.